2005
DOI: 10.1258/135581905774414259
|View full text |Cite
|
Sign up to set email alerts
|

Using pharmacy data to identify those with chronic conditions in Emilia Romagna, Italy

Abstract: Using Italian automated pharmacy data, a measure of population-based chronic disease status was developed. Applying the model to pharmaceutical claims from Emilia Romagna 2001, a large proportion of the population was identified as having chronic conditions. Pharmacy data may be a valuable alternative to survey data to assess the extent to which large populations are affected by chronic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 0 publications
6
61
0
2
Order By: Relevance
“…We found that the largest proportions of persons suffered from pain, rheumatologic conditions and cardiovascular diseases, including hypertension. These findings are in line with previous studies in Italy estimating prevalence of chronic diseases showing highest rates in cardiovascular diseases and rheumatologic conditions [12,13]. On the other hand, our results are different from the Dutch estimates based on the PCG-model showing a low prevalence rate in rheumatologic conditions [19].…”
Section: Discussionsupporting
confidence: 73%
“…We found that the largest proportions of persons suffered from pain, rheumatologic conditions and cardiovascular diseases, including hypertension. These findings are in line with previous studies in Italy estimating prevalence of chronic diseases showing highest rates in cardiovascular diseases and rheumatologic conditions [12,13]. On the other hand, our results are different from the Dutch estimates based on the PCG-model showing a low prevalence rate in rheumatologic conditions [19].…”
Section: Discussionsupporting
confidence: 73%
“…Comorbidities were ascertained from non-cardiac hospital admissions with primary diagnoses for other conditions that may increase mortality risk [18]. We also used the Chronic Condition Drug Group (CCDG), a prescription drug-based comorbidity index [19]. CCDGs were developed in the same RER database and have been applied in other published studies [14,15,20].…”
Section: Covariatesmentioning
confidence: 99%
“…As a result, there are multiple data features that could potentially be used for case ascertainment. For example, osteoporosis drug treatments have been proposed for case ascertainment in pharmacy databases [10,21].…”
Section: What Is New?mentioning
confidence: 99%